Persepsi Siswa tentang Implementasi Media Literasi Digital di Pembelajaran Daring Geografi [Students' Perception about the Implementation of Digital Literacy in Geography Online Learning] - Apriyanti, Maria Eti; Purbojo, Rijanto (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
The background of this research is the low literacy, participation, and collaboration ability of students. The COVID-19 pandemic has had an impact on the learning process. This study aims to determine student perceptions related to the implementation of digital literacy media on participation, collaboration skills, student satisfaction, and cognitive learning achievement in geography subjects. The subjects in this study were 162 students of class XI and XII social studies at XYZ private high school in South Tangerang. This research is a quantitative descriptive study using a simple regression test to measure. Data collection techniques using a questionnaire in the form of google form. The research instrument used is a variable to measure students' perceptions about the implementation of digital literacy, participation, collaboration skills, and student satisfaction. The results showed that students' perceptions about the implementation of digital literacy media affected the participation of 38.2%. Students' perceptions of digital literacy media also affect 50.2% of collaboration skills and 64.3% of student satisfaction. Participation and collaboration ability did not show any effect on cognitive learning achievement, it was seen from the sig value. > 0.05 and Fcount. < Ftable. Cognitive learning achievement is influenced by student satisfaction and perceptions regarding digital literacy media in geography online learning by 5.4% and 2.5%, respectively. So it can be concluded that students' perceptions of digital literacy media help students learn in geography online learning.